2008
DOI: 10.3164/jcbn.2008054
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of Selected Food Phytochemicals on CD74 Expression in NCI-N87 Gastric Carcinoma Cells

Abstract: Summary Helicobacter pylori (H. pylori) is one of the most widespread human pathogens, and plays major roles in chronic gastritis and gastric cancer. CD74 of gastric epithelial cells has recently been identified as an adhesion molecule to urease in H. pylori. In this study, we found that CD74 is highly expressed in a constitutive manner in NCI-N87 human gastric carcinoma cells at both the protein and mRNA levels as compared with Hs738St./Int fetal gastric cells. Subsequently, a novel cell-based ELISA able to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 63 publications
0
26
0
3
Order By: Relevance
“…At these concentrations, 200 ml of grapefruit juice contains 1.5 mg BG, 1.8 mg BT and 0.75 mg DHB. Bergamottin interferes with CYP3A4 cytochrome P450 [33][34][35][36][37][38] , and is reported to have anticarcinogenic activity 39,40) , anti-tumor cell invasion 41) and suppress Helicobacter pylori 42) . Bergamottin also activates peroxisome proliferator-activated receptor α (PPARα) or PPARγ, induces adiponectin secretion and inhibits very lowdensity lipoprotein (VLDL) in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…At these concentrations, 200 ml of grapefruit juice contains 1.5 mg BG, 1.8 mg BT and 0.75 mg DHB. Bergamottin interferes with CYP3A4 cytochrome P450 [33][34][35][36][37][38] , and is reported to have anticarcinogenic activity 39,40) , anti-tumor cell invasion 41) and suppress Helicobacter pylori 42) . Bergamottin also activates peroxisome proliferator-activated receptor α (PPARα) or PPARγ, induces adiponectin secretion and inhibits very lowdensity lipoprotein (VLDL) in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It is known to potentiate the action of the chemotherapeutic agent Tamoxifen(tm) in the treatment of melanoma by making the cancerous cells more amenable to removal through freezing them off the skin (Piantelli et al, 2001). In cases where persistent H. pylori infection (now understood to be the cause of most stomach ulcers) has been so persistent and inflammatory as to induce stomach cancer, quercetin, along with nobiletin and bergamottin, have been found to decrease the adhesion rate of the offending bacteria and to disrupt the cellular production of CD74, a protein necessary for gastric carcinoma cells to thrive (Sekiguchi, Washida, & Murakami, 2008 Oka, 1995), improves normal cell-to-cell communication in a way that inhibits the advance of liver cancers in the lab (Chaumontet et al, 1997), and has been shown to forestall organ-to-organ metastases in organ tissues cultured in the lab (Bracke, Vyncke, & Van Larebeke, 1989). Pretreatments with tangeretin sensitize human ovarian cancer cells that otherwise have become resistant to the chemotherapeutic drug, cis-platin, promoting their apoptosis and disrupting their proliferative mitosis (Arafa et al, 2009).…”
Section: Citrus Oil Pulp Seed and Juice Components As Anticancer Amentioning
confidence: 99%
“…In addition, anticancer [9,10] , immunomodulatory [11] , antibacterial [12] , antioxidant [13] and neuroprotective functions [14] have also been shown. Psoralens, extremely toxic to a wide variety of prokaryotic and eukaryotic organisms, are mainly extracted from the ripe fruit of Psoralea corylifolia (Leguminosae), an erect annual herb widely used in Ayurvedic medicine and traditional Chinese medicine.…”
Section: Topic Highlightmentioning
confidence: 99%
“…In Asian countries such as Mongolia, when people were infected with Helicobacter pylori, an alternative non-antibiotic method based on green tea catechins was found to strongly inhibit H. pylori urease activity in vitro and to suppress the bacterialinduced gastritis [22] . A few years later, in a cohort study of gastric carcinomas after screening a total of 25 food phytochemicals, bergamottin was designed as the most promising agent [12] . Grapefruit and grapefruit-based products are rich in flavonoids, coumarins and carotenoids, which in the long run have been shown to have antiinflammatory [23] , anticarcinogenic [9,10,24] , antibacterial [12] activities and significant protective effects on cardiovascular diseases [9,13] .…”
Section: Effects On Normal Cellsmentioning
confidence: 99%
See 1 more Smart Citation